Diseño de unidades didácticas mediante el aprendizaje basado en problemas para la enseñanza de las ciencias - Flórez-Nisperuza, Elvira-Patricia; González-Rivas, Martha-Sofía (Revista Científica, 2020)
The objective of this study was to analyze appropriation of science and, based on this, to propose the design of contextualized didactic units through problem-based learning (PBL). This work is part of a qualitative research through a case study design carried out from the analysis of the classroom context, with a self-evaluation exercise performed with 32 eleventh grade students from a public education institution in the Colombian Caribbean, in addition to interviews with eight of their natural science teachers. The findings of this research show that most of the students are unaware of the importance of scientific competences, which is evidenced in a low level of appropriation when learning the concept of ‘human influence on the dynamics of ecological populations’. Similarly, teachers declare little use of teaching methodologies and strategies that favor the learning and development of scientific competencies. Therefore, the implementation of a didactic proposal related to the design of didactic units under the PBL approach is suggested for the teaching of natural sciences.